2008
DOI: 10.1111/j.1399-3054.2008.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐photochemical loss in PSII in high‐ and low‐light‐grown leaves of Vicia faba quantified by several fluorescence parameters including LNP, , a novel parameter

Abstract: Using the expression of fluorescence originated from the PSII open reaction center in the light by Oxborough and Baker (1997), we obtained a formula that expresses relationships between the quantum efficiency of PSII photochemistry in the dark (Phi(m)= F(v)/F(m)) and in the light Phi'(m)=F'(v)/F'(m):Phi'(m)=Phi(m)+L(NP), where L(NP)(=F(0)/F'(m)) denotes the quantum yield of light induced non-photochemical losses (heat dissipation and fluorescence de-excitation) in PSII. Using L(NP) and other conventional fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…However, in this study, no clear relationship was observed between F v '/F m ' and φ PSII values and those non-photochemical quenching (qNP). In this development stage, decreases in F v '/F m ' and φ PSII were followed by the slight increase (but not significant) in L NP , corroborating the statement made by Lu et al (2002) and Stefanov and Terashima (2008). qNP was higher in BRS Pelota until 6 DAH.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, in this study, no clear relationship was observed between F v '/F m ' and φ PSII values and those non-photochemical quenching (qNP). In this development stage, decreases in F v '/F m ' and φ PSII were followed by the slight increase (but not significant) in L NP , corroborating the statement made by Lu et al (2002) and Stefanov and Terashima (2008). qNP was higher in BRS Pelota until 6 DAH.…”
Section: Resultssupporting
confidence: 86%
“…Therefore, this variation was similar between rice varieties, showing that the two rice varieties present the same efficiency of use the excitation energy during the light-adapted state. According to Stefanov and Terashima (2008), decreases in F v '/F m ' and φ PSII could be associated with an increased non-photochemical loss. However, in this study, no clear relationship was observed between F v '/F m ' and φ PSII values and those non-photochemical quenching (qNP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Light energy absorbed by Chl molecules can undergo three fates: (1) be used to drive photosynthesis, (2) excess energy can be dissipated as heat (nonphotochemical quenching) or, (3) re-emitted as light-Chl fluorescence (Maxwell and Johnson 2000, Stefanov and Terashima 2008, Vredenberg 2008. Thus, photoprotection mechanisms could be different between leaves in full sun and those in shade.…”
Section: Introductionmentioning
confidence: 98%
“…Chl fluorescence has been increasingly used to examine both the mechanism of photosynthesis and whether the plants are influenced by environmental stress (Van Kooten et al 1990, Lovelock et al 1998, Khan et al 2000. Light energy absorbed by Chl molecules can undergo three fates: (1) be used to drive photosynthesis, (2) excess energy can be dissipated as heat (nonphotochemical quenching) or, (3) re-emitted as light-Chl fluorescence (Maxwell and Johnson 2000, Stefanov and Terashima 2008, Vredenberg 2008.…”
Section: Introductionmentioning
confidence: 99%